Children’s Creativity and Personal Adaptation Resources - Vera G. Gryazeva-Dobshinskaya; Yulia A. Dmitrieva; Svetlana Yu. Korobova; Vera A. Glukhova (Behavioral Sciences, 2020)
The study provides insights into the aspects of creativity, the structure of psychometric intelligence, and personal adaptation resources of senior preschool children. Creativity and intelligence are presented as general adaptation resources. Existing studies of creative ability and creativity as integral individual characteristics in the context of adaptation are analyzed. The aim is to identify varied sets of creativity and personal adaptation resource markers that differentiate groups of children in order to determine possible strategies for adaptation, preservation, and development of their creative abilities at the beginning of lyceum schooling. It embraces the use of the E. Torrance Test of Creative Thinking (TTCT) (figural version), the Wechsler Intelligence Scale for Children (WISC), and the G. Rorschach Test. A sample of the study consisted of 122 children, aged 6−7 and enrolled in a school. The average IQ score among the children was above 115 (M = 133.7, σ = 9.9). The entire sample was divided into four groups by the originality-elaboration ratio according to the TTCT. The correctness of the children’s division into the groups according to the markers of creativity and personal adaptation resources is confirmed by the discriminant analysis. We have identified the factor structure of creativity, intelligence, and personal adaptation resources in the entire sample of children and in each of the groups. In the group of preschoolers with high originality and elaboration, the resulting structure integrated the components of creativity with personal adaptation resources and intelligence scores. In the group of children with a low level of originality and elaboration, the markers of creativity, intelligence, and personal adaptation resources are not interlinked.